Lippincott certification review : pediatric acute care nurse practitioner - Kline-Tilford, Andrea M.; Haut, Catherine (Wolters Kluwer, 2016)
"Lippincott Certification Review: Pediatric Acute Care Nurse Practitioner is the ideal companion while preparing for the Acute Care CPNP(r) exam administered by the Pediatric Nursing Certification Review Board, or for anyone who seeks to perform at a higher level of practice for children who are acutely, chronically, and critically ill. The AC PNP (Acute Care Pediatric Nurse Practitioner) program is designed to prepare experienced pediatric nurses to meet the specialized physiologic and psychological needs of infants, children, adolescents and young adults with complex acute, critical and chronic health conditions. The focus of AC PNP care includes complex monitoring and ongoing management of intensive therapies in a variety of settings, including but not limited to, inpatient and outpatient hospital settings, emergency departments and home care settings. Specialty areas of practice are varied and continue to emerge. AC PNPs collaborate with an interprofessional team to provide optimal patient care. The Certified Pediatric Nurse Practitioner: Acute Care (CPNP-AC) certification exam was developed by the Pediatric Nursing Certification board nearly 10 years ago. Since that time, there has not been a review book specific to this exam, and students have been seeking preparation materials for the exam. For the (approximately) 26 programs in the United States offered to complete pediatric certification, this book is the only available certification review material for the exam. Organized in a simple, bulleted format, this invaluable resource includes multiple choice self-assessment questions with rationales at the end of every chapter, plus two self-assessment exams with rationales - totaling more than 750 questions. Content focuses on the diagnosis and management of pediatric acute care problems typically treated in the emergency department or an inpatient setting._ Certification must be renewed every five years._"--